Facilitating use of ICT in creating knowledgeable youth fishermen - Omar, Siti Zobidah; Chhachhar, Abdul Razaque; Bolong, Jusang; Mohamed Shaffril, Hayrol Azril (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
The role of information and communication technology towards the society cannot be denied. ICT has played a vital role in the development particularly in different sector of the society such as agriculture, education, health, economic and fisheries. In agriculture sector, the fishing industry is playing an important role in the Malaysian economic development. Base on the scenario above the purpose of this study is to examine the level use of ICT tools among the youth fishermen in the northern part of Peninsular Malaysia. A quantitative approach was employed in this study by using a survey questionnaire to generate the primary data of the study. A total of 200 respondents, comprising of male and female fishermen from the Perak and Kedah states of Malaysia have been selected as the main respondents of the study. The results shows that the among ICT tools that frequently used by the youth fishermen is a mobile phone, followed by television and GPS. The purpose of using this technology is to get information pertaining to the fisheries industry such as weather, market, safety and others. Mobile phone communication help them in getting fast feedback, prompt action taken and thus help in enhancing their income generation, increase their knowledge and have a control on their daily fisheries industry task at a reasonable and lower cost. It is suggested that a mobile application communication platform pertaining to the fisheries being set-up, to enable the young fishermen to communicate, exchange information among themselves and thus helping to further enhance their knowledge, increase the income generation and to prepare the dynamic youth fishermen to enable them to compete with the world global fisheries industry at the international level.